Employment growth of new firms - Erik Stam; Petra Gibcus; Jennifer Telussa; Elizabeth Garnsey (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This paper analyses the association between dynamic capabilities and new firm growth, controlling for measures of firm resources, characteristics of the entrepreneur, and aspects of the environment. The central research question is: How strong is the relationship between dynamic capabilities and the growth of new firms? The paper opens with a review of empirical studies on employment growth in new firms and then moves on to a discussion on the role of dynamic capabilities in the explanation of new firm growth. After a description of the data and variables the results and implications of this study are discussed.
Keywords: D21; L23; L25; L26; M13; M21; 330; new firms; firm growth; innovation; dynamic capabilities; Unternehmensgründung; Unternehmenswachstum; Beschäftigungseffekt; Innovation; Niederlande